Determinant of Stock Prices for Nickel Companies in Indonesia - Puspitawati, Eka; Rozi, Fakhrur; Alamsyah, Muhammad Royhan (Universitas Negeri Semarang, 2025)
Nowadays, nickel is an important component of batteries which is a very profitable subsector. The increasing public interest in electric vehicles and renewable energy is one of the causes of the high demand for nickel for electric vehicles and increasing attention for public companies of nickel processing. This study’s objective is to analyze factors determining the stock prices of nickel companies registered on the Indonesia Stock Exchange (IDX). The tested factors include Total Asset Turnover Ratio (TATO), Return on Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Price to Earning Ration (PER), Price to Book Value (PBV), and Earning per Share (EPS). This research applies data of 3 Indonesian nickel companies from q12014 to q32022, and applies a method of panel data. Findings of this study reveal that ROE, DER, PBV, and EPS have impacts significantly on the stock prices of Indonesian nickel companies. Indonesian nickel companies are suggested to investing smelters in order to optimize the added value of nickel commodities and follow the downstream policy.